State and development prospects of dental care for the Ukrainian population - O. V. Voznyi; S. M. Hermanchuk; V. I. Struk; V. I. Bida; A. V. Pohorila (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The results of epidemiological studies and statistics of the Ministry of Health of Ukraine show that in recent years, the level of dental morbidity in Ukraine remains high. Late dental care causes such complications as partial and total loss of teeth, aesthetic and functional disorders, and requires dental rehabilitation with the use of complex structures of dentures.